"Gusła nasze moc straciły" Czy kultura współczesna stawia "Dziadom" ważkie pytania ? - Woźniewska-Działak, Magdalena (Colloquia Litteraria, 2014)
‘Gusła nasze moc straciły’. Does contemporary culture ask Dziady serious questions? Review of a theatre spectacle: Adam Mickiewicz, Dziady, parts I, II and IV and the poem Upiór, directed by Michał Zadara, Teatr Polski in Wrocław, premiere on 14th February 2014. The review article discusses Dziady, część I, II i IV and the poem Upiór directed by Michał Zadara. The spectacle is part of a bigger project realised at Teatr Polski in Wrocław in 2014–2016. The article attempts to reconstruct the director’s idea of a stage version of Mickiewicz’s drama, which is regarded in Polish culture as a symbolic work constituting Polish identity. Furthermore, the author asks a number of questions about the condition of the contemporary culture that seems to be a culture of exhaustion, and also about this culture’s dispositions and capabilities employed when reinterpreting the romantic masterpiece.